2021
DOI: 10.1371/journal.pone.0249999
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary pro inflammatory cytokines profile level in patients treated with labial and lingual fixed orthodontic appliances

Abstract: The secretions of certain cytokines, chemokines and growth factors are triggered by orthodontic appliances, which often affect the remodelling of periodontal tissues. Critical cumulative forces are applied by various types of orthodontic appliances to the periodontium. The secretion of such molecules is probably responsible, through molecular and cellular communications, for the optimal resorption of hard tissues in the periodontal setting, which therefore enables the coordination of multiple movements of toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The cytokine levels were measured in the culture supernatants of splenocytes, and in the collected saliva and tears as described before [ 9 , 17 , 18 ], with some modifications. In brief, the isolated splenocytes were suspended in RPMI 1640 medium supplemented with 10%FBS and 1%penicillin/streptomycin (100 U/ml,100μg/mL) and were stimulated with anti-CD3 and anti-CD28 at 37°C in a humidified 5%CO2 chamber for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The cytokine levels were measured in the culture supernatants of splenocytes, and in the collected saliva and tears as described before [ 9 , 17 , 18 ], with some modifications. In brief, the isolated splenocytes were suspended in RPMI 1640 medium supplemented with 10%FBS and 1%penicillin/streptomycin (100 U/ml,100μg/mL) and were stimulated with anti-CD3 and anti-CD28 at 37°C in a humidified 5%CO2 chamber for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the salivary TNF-α level in pregnant women, especially those who are obese, can affect the weight of the infant [ 35 ]. On the other hand, tooth movement caused by orthodontic force may increase salivary TNF-α [ 36 ] and IL-6 levels [ 14 ]. It can be concluded that, in the absence of pregnancy, the concentration of salivary IL-6 and TNF-α increases due to orthodontic appliance use.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to orthodontic treatment, IL-6 plays an important role in the movement of teeth, namely the inflammatory process that supports the resorptions process in apical areas [ 12 , 13 ]. Increased IL-6 levels occur not only in periodontal or alveolar tissues but also in saliva [ 14 ]. Similar to IL-6, TNF-α is also affected by orthodontic treatment and plays a role in the processes of tooth movement and bone resorption [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bead assay LEGENDplex™ Human Inflammation Panel 1 (13-plex) with V-bottom Plate (BioLegend, San Diego, CA, USA), previously used successfully with saliva samples [12,13], was used to quantify inflammatory markers (IL-1β, IFN-α2, IFN-γ, TNF-α, MCP-1, IL-6, IL-8, IL-10, IL-12p70, IL-17A, IL-18, IL-23, and IL-33) in oral samples from intervention and control groups.. Specifically, the supernatants obtained after sample centrifugation for 10 min at 10.000g, from the intervention (at baseline (M0), after 1 month of PR (M1), and after 3 months of PR (M3)) and control groups (in the timepoints M0, M1 and M3), were used for cytokine quantification following manufacturer’s recommendations [14].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the oral and lower airway microbiotas are highly correlated [10], given the topological continuity between the niches, implying oral bacteria as the major colonizers of the lungs through aspiration [10][11][12].…”
Section: Introductionmentioning
confidence: 99%